2019
DOI: 10.1049/mnl.2018.5342
|View full text |Cite
|
Sign up to set email alerts
|

ZnO ultraviolet photodetector based on flexible polyester fibre substrates by low‐temperature hydrothermal approach

Abstract: The development of flexible photodetectors is believed to have great potential for future optoelectronic applications, such as biomedical imaging and smart wearable systems. Here the work proposes a simple and low-cost approach for integrating a flexible and wearable ZnO ultraviolet (UV) photodetector using polyester fabric as the platform for the first time. The ZnO nanowires coated polyester fabric was prepared by a low-temperature hydrothermal approach. They measured the performance of the photodetector in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A key aspect of developing ZnO-based wearable technologies is to develop the ability to grow their unique morphologies on flexible substrates. [80] To this end, ZnO nanostructures have been fabricated on a wide variety of flexible substrates, such as polyimide (PI), [72c,73c,81] polyester, [82] polyethersulfone (PES), [81a] polyetherimide (PEI), [83] polyethylene terephthalate (PET), [84] polyvinylalcohol (PVA), [85] polyvinyl chloride (PVC), [72a] PDMS, [86] polytetrafluoroethylene (PTFE or Teflon), [87] mica, [88] and paper. [39,73a,89] One popular choice of the substrate has been paper-based devices as they are low cost, lightweight and readily available.…”
Section: Zno-based Uv Sensorsmentioning
confidence: 99%
“…A key aspect of developing ZnO-based wearable technologies is to develop the ability to grow their unique morphologies on flexible substrates. [80] To this end, ZnO nanostructures have been fabricated on a wide variety of flexible substrates, such as polyimide (PI), [72c,73c,81] polyester, [82] polyethersulfone (PES), [81a] polyetherimide (PEI), [83] polyethylene terephthalate (PET), [84] polyvinylalcohol (PVA), [85] polyvinyl chloride (PVC), [72a] PDMS, [86] polytetrafluoroethylene (PTFE or Teflon), [87] mica, [88] and paper. [39,73a,89] One popular choice of the substrate has been paper-based devices as they are low cost, lightweight and readily available.…”
Section: Zno-based Uv Sensorsmentioning
confidence: 99%
“…These ZnO photodetectors exhibited a stable response with high photocurrent to dark current ratios. 162 Li et al utilized the sandwich metal−semiconductor−metal structure to fabricate ultraviolet photodetectors. 22 In this work, vertically aligned ZnO nanowires were grown on Ag nanowire networks followed by the deposition of another Ag nanowire layer on the top.…”
Section: Fabrication Technique Of Wbg Materials For Wearable and Impl...mentioning
confidence: 99%
“…By utilising the lowtemperature hydrothermal method, the authors successfully demonstrated the controlled growth of ZnO NWs on soft fabric substrates for the first time. These ZnO photodetectors exhibited a stable response with high photocurrent to dark current ratios(162). Li et al utilised the sandwich metalsemiconductor-metal structure to fabricate ultraviolet photodetectors(22).…”
mentioning
confidence: 99%
“…5 The band gap of ZnO is 3.37 eV, and the corresponding absorption wavelength is in the UV band. 6,7 Therefore, it shows that ZnO is an exceedingly good UV PD material. ZnO-based UV PDs have been widely researched and commercialized because of their good stability, low cost, and nice sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the improvement of social needs and people’s lives, UV PDs have become important devices for human activities. UV PDs have been widely used in military fields and commercial, such as gas sensing, missile detection, flame sensing, UV guidance, fire detection, environmental monitoring, medical applications, and optical communications . The band gap of ZnO is 3.37 eV, and the corresponding absorption wavelength is in the UV band. , Therefore, it shows that ZnO is an exceedingly good UV PD material. ZnO-based UV PDs have been widely researched and commercialized because of their good stability, low cost, and nice sensitivity.…”
Section: Introductionmentioning
confidence: 99%